The enterprise for ASEAN initiative in the emerging Asia-Pacific context a politico-economic assessment - Naya, Seiji F.; Plummer, Michael G. (2006)
Although economic integration under the rubric of the Asia-Pacific Economic Cooperation (APEC) has been relatively lackluster, bilateral and regional accords in the Asia-Pacific region have been proceeding at an unprecedented pace. This paper considers the economics and political economy of the US-ASEAN Enterprise for Asean Initiative (EAI) in the context of the rapidly changing policy environment in Asia. The paper gives an extensive review of the Asean Economic Integration and 'ASEAN Plus Three' Initiatives, in addition to a statistical and econometric treatment of the us-asean economic relationship and the implications of the EAI. It concludes that the EAI makes sense for the United States and ASEAN from both economic and politico-economic perspectives.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 49)
Keywords: International economic integration; International economic relations; Southeast Asia. -- Economic integration